2023
DOI: 10.1007/s10803-023-05901-2
|View full text |Cite
|
Sign up to set email alerts
|

The Social Shapes Test as a Self-Administered, Online Measure of Social Intelligence: Two Studies with Typically Developing Adults and Adults with Autism Spectrum Disorder

Abstract: The Social Shapes Test (SST) is a measure of social intelligence which does not use human faces or rely on extensive verbal ability. The SST has shown promising validity among adults without autism spectrum disorder (ASD), but it is uncertain whether it is suitable for adults with ASD. We find measurement invariance between adults with ( n = 229) or without ASD ( n = 1,049) on the 23-item SST. We also find that adults without ASD score higher on the SST than adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…In both SJTs, all items were presented on one page. Test instructions were shown on a separate page before the SJT as well as on top of the page with the actual test items (for the instruction we used for the SST, see [37]). In the SST, participants had the option to view the videos as many times as they liked.…”
Section: Sample and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In both SJTs, all items were presented on one page. Test instructions were shown on a separate page before the SJT as well as on top of the page with the actual test items (for the instruction we used for the SST, see [37]). In the SST, participants had the option to view the videos as many times as they liked.…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…Finally, the highly significant, albeit rather weak, correlation (r = 0.26, p = < 0.001) between the SST and the HAM-SJT (see Table 2) indicates that the SST measures similar aspects to the HAM-SJT. However, test developers of the SST could already show promising convergent validity with some SJTs and other performance measures of social competence [28,37]. For its use in the medical school admission context, however, more studies are required first.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Brown et al (2019) report a full account of the initial development and validity evidence for the SST among typically-developing adult samples and more recent research has demonstrated convergent validity with effective judgment in social situations in the workplace (Brown et al, 2022) along with performance on similar animated shape tasks (Brown et al, 2021). The validity of animated shape tasks has been demonstrated in clinical and developmental research, including in identifying difficulties in social attribution among individuals diagnosed with autism spectrum disorder or schizophrenia (Burger-Caplan et al, 2016;Brown, Heck, & Chabris, 2023;Johannesen et al, 2018;Martinez et al, 2019;Wilson, 2021). The SST therefore shows promise as an effective measure of social intelligence in clinical and non-clinical populations.…”
Section: Objective Social Intelligencementioning
confidence: 99%
“…Data were analyzed using R, version 3.6.1 (R Core Team, 2019). The data reported in this study were collected as part of a test-retest reliability study reported in Brown et al (2023).…”
Section: Transparency and Opennessmentioning
confidence: 99%